The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1086/663598
|View full text |Cite
|
Sign up to set email alerts
|

From Rodent Utopia to Urban Hell: Population, Pathology, and the Crowded Rats of NIMH

Abstract: In a series of experiments at the National Institute of Mental Health, the animal ecologist John B. Calhoun offered rats everything they needed, except space. The resulting population explosion was followed by a series of "social pathologies"--violence, sexual deviance, and withdrawal. This essay examines the influence of Calhoun's experiments among psychologists and sociologists concerned with the effects of the built environment on health and behavior. Some saw evidence of the danger of the crowd in Calhoun'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…4 In the following decades, psychologists such as Mark Rosenzweig followed up on these observations, systematically comparing the performance of rats raised alone in standard cages on learning and memory tests with rats raised together in cages with objects such as running wheels, tunnels and toys (see for example Bennett et al, 1964). Similar lines of research on the impact of the physical configuration of living spaces on rodent behavior were also present in ecology (Ramsden, 2011) and ethology (Kirk, 2009) during this period.…”
Section: Multiple Meanings Of the Home Cage Environmentmentioning
confidence: 98%
See 1 more Smart Citation
“…4 In the following decades, psychologists such as Mark Rosenzweig followed up on these observations, systematically comparing the performance of rats raised alone in standard cages on learning and memory tests with rats raised together in cages with objects such as running wheels, tunnels and toys (see for example Bennett et al, 1964). Similar lines of research on the impact of the physical configuration of living spaces on rodent behavior were also present in ecology (Ramsden, 2011) and ethology (Kirk, 2009) during this period.…”
Section: Multiple Meanings Of the Home Cage Environmentmentioning
confidence: 98%
“…One research team showed, for example, that they could alter the performance of the so-called 'maze bright' and 'maze dull' rats (bred for a hereditary predisposition to high or low performance in maze experiments) by raising them in enriched or impoverished environments (Cooper and Zubek, 1958). Such experiments with rodent housing became widely influential in broader academic and public debates in the 1960s and 1970s about the role of the built environment in human society and how it contributed to anti-social or pathological behaviors (Ramsden, 2011). Interest in environmental enrichment in rodent research (as measured by the number of citations on the topic) grew steadily throughout the remainder of the twentieth century as the techniques of enrichment were incorporated into new research agendas (Hutchinson et al, 2005).…”
Section: Multiple Meanings Of the Home Cage Environmentmentioning
confidence: 99%
“…According to Calhoun, humans were capable of constructing “conceptual space” through role differentiation and new methods of communication. High density could be made beneficial by better designing urban environments, and all this would bring about a sense of responsibility and compassion, ultimately leading to a decline in fertility (Calhoun, ; Ramsden, , pp. 661, 671).…”
Section: Inspiration and Justification From Ethologymentioning
confidence: 99%
“…Perhaps, this ultimately common goal helped those environmental psychologists who were critical of biological explanations to be quite tolerant of their design‐oriented colleagues, as well as of psychologists using biological reasoning, and to give recognition to their results. The criticism toward “design‐determinism” expressed by some urban sociologists (Ramsden, , p. 684) was not seen among psychologists. It is likely, however, that this tolerance was partially due to the goal of developing the field and building a disciplinary identity; the existence of a wide variety of paradigms was pointed out neutrally (e.g., Craik, ; Stokols, , p. 257).…”
Section: Conclusion—from Territorial Aggression To Place Identitymentioning
confidence: 99%
“…This is so not only because of a long history of STS discussing the topic of boundary creation and maintenance (Gieryn 1983) but because we know that Durkheim was active and purpositive in determining what did and did not count as 'social' (Ramsden & Wilson 2014: 204) and that the act of demarcating the border between social psychology and sociology was itself important in determining what 'the social' these disciplines forged actually looked like (Greenwood 2004). Indeed, a consideration of psychology greatly complicates many of Political Biology's core claims: Psychology is a discipline where, post WW2, biosocial science was flourishing (Ramsden 2011) and key thinkers like B.F. Skinner were producing utopian novels -both trends Meloni insists were typical of biology in the early twentieth century instead occurring when epistemic shifts suggest that the activities should have been largely unthinkable.…”
Section: Reviewmentioning
confidence: 99%